Post conflict prosecution of gender-based violence : a comparative analysis of the International Criminal Tribunal for Rwanda (ICTR), the International Criminal Tribunal for the former Yugoslavia (ICTY) and the Special Court for Sierra Leone (SCSL) - Botha, C.J. (Christo J.) (University of Pretoria, 2013)
Dissertation (LLM)--University of Pretoria, 2011.